2014
DOI: 10.1128/cmr.00112-13
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and Clinical Manifestations of Enteroaggregative Escherichia coli

Abstract: SUMMARY Enteroaggregative Escherichia coli (EAEC) represents a heterogeneous group of E. coli strains. The pathogenicity and clinical relevance of these bacteria are still controversial. In this review, we describe the clinical significance of EAEC regarding patterns of infection in humans, transmission, reservoirs, and symptoms. Manifestations associated with EAEC infection include watery diarrhea, mucoid diarrhea, low-grade fever, nausea,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
125
4
8

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(159 citation statements)
references
References 159 publications
6
125
4
8
Order By: Relevance
“…In addition, EAEC was one of major causes of diarrhea outbreak in some developed countries (e.g. Europe, the UK and Japan) [31, 38]. EAEC was not the important bacterial pathogen associated diarrhea in individuals over 5 years in present study, and similar conclusion was obtained from other study [32].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In addition, EAEC was one of major causes of diarrhea outbreak in some developed countries (e.g. Europe, the UK and Japan) [31, 38]. EAEC was not the important bacterial pathogen associated diarrhea in individuals over 5 years in present study, and similar conclusion was obtained from other study [32].…”
Section: Discussionsupporting
confidence: 88%
“…EAEC is also the leading cause of diarrhea in children, adult and HIV-positive patients worldwide [37, 38]. In addition, EAEC was one of major causes of diarrhea outbreak in some developed countries (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, strains expressing the aggR regulon are denoted as typical EAEC [25]. In most epidemiological studies on EAEC, typical EAEC strain has been mainly targeted because many investigators have found a strong association between these and diarrhea [19, 26, 27], which is consistent with our study. ETEC was reported as the second most common DEC isolated in this study.…”
Section: Discussionsupporting
confidence: 88%
“…The pathogenesis of EAEC infection involves the adherence of the bacterium to the intestinal mucosa, followed by the secretion of one or more enterotoxins and/or cytotoxins that induce mucosal inflammation (9). EAEC adherence to the mucosa is characterized by the formation of a thick biofilm (10), which may promote persistent infection.…”
mentioning
confidence: 99%